2015
DOI: 10.11604/pamj.2015.20.139.4810
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the diagnostic methods for Group A streptococcal sore throat in two reference hospitals in Yaounde, Cameroon

Abstract: IntroductionSore throat is a common complaint in general practice which is more frequent in children. The most frequent pathogenic bacteria associated with this infection is Streptococcus pyogenes. Rapid Antigen Diagnostic Test (RADT) facilitates the rapid identification and consequently prompt treatment of patients, prevents complications, and also reduces the risk of spread of Group A Streptococcus (GAS). The main objective of this study was to assess the diagnostic value of a rapid streptococcal antigen det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Afrika'da yapılan bir çalışmada, GAS prevalansı %22.5 olarak belirlenmiştir (16) . Mısır'da 4-16 yaş arası hastaları kapsayan bir çalışmada ise GAS prevalansı %42.2 olarak bildirilmiştir (17) .…”
Section: Discussionunclassified
“…Afrika'da yapılan bir çalışmada, GAS prevalansı %22.5 olarak belirlenmiştir (16) . Mısır'da 4-16 yaş arası hastaları kapsayan bir çalışmada ise GAS prevalansı %42.2 olarak bildirilmiştir (17) .…”
Section: Discussionunclassified
“…These outcomes contradict with foregoing studies, which comparatively reported stumpy specificity and sensitivity of brisk antigen test while juxtapose by throat culture. [17][18][19][21][22] Statistical contradictions might be result of different techniques of laboratory. For throat swab, throat culture and screening test, our technicians adopted standard techniques.…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was calculated using the population proportion formula which is based on the assumption of 5% error, 95% confident values (Z1-α/2=1.96) and 13.5% prevalence based on a similar study in Yaounde, Cameroon (Gonsu et al, 2015). The convenient samping method was used because we recruited the participants as they presented at the pediatric ward after diagnosis.…”
Section: Samplingmentioning
confidence: 99%
“…A study carried out in Cameroon by Hardis revealed that, streptococcal pharyngitis represent 8.49% of inflammation pathologies that affect the ear, nose and the throat. It was also revealed that, it is most frequent in age groups 3 -30 years (Gonsu et al, 2015). GAS transmission can be through direct contact, or food borne contamination or droplets from those with pharyngeal infection or colonization (Kebede et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%